anonymous
  • anonymous
solve the systems of equations by subsitition 4x -3y =3 6x-2y =2
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
schrodinger
  • schrodinger
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Y=-1 X= 7/-3
anonymous
  • anonymous
how did you get that can you show me
anonymous
  • anonymous
oh wait..

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
apologies, x is 0 and y is -1
anonymous
  • anonymous
can you show me how you got it
anonymous
  • anonymous
basically multiply the first equation by 6 to get 24X-18Y=18 and then similarly the second equation by 4 to get 24X-8Y=8 then subract the seconds equation from the first; 24X-18Y=18 -(24X-8Y=8) To get; -10Y = 10 Rearannge to get Y=10/-10 hence Y=-1 Subsitute into first equation to get 4X+3=3 hence 4X=0 so x is 0

Looking for something else?

Not the answer you are looking for? Search for more explanations.